Retrospective study on the cytological exams in a veterinary technic hospital in a five year period - Rosolem, M. C. [UNESP]; Moroz, L. R.; Rodigheri, S. M. [UNESP]; Corrêa Neto, U. J.; Porto, C. D.; Hanel, J. S. (FapUNIFESP (SciELO), 2013)
The cytological exam is a practical diagnostic aplication which allows the detection of inflammatory, proliferative and infectious disturbances. In the present study, the results of cytological exams during six years were evaluated, determining the most common type of disorder (inflammatory, infectious, proliferative). Epidemiological aspects such as species, breed, sex and age were taken into account. 270 reviews were evaluated and the prevalence was neoplasms (53%). The canine specie was the most observed, with 92% of cases. Females totaled 53%. The age ranged from one to 17 years and the interval of six to 10 years was most observed (40% of cases). The round cell neoplasms were the most prevalent, followed by breast neoformations.
Keywords: Aspiration cytology; Domestic small animals; Neoplasm